Application of mathematical optimization in decision making relevant to the resilience of national security: networked society as the basis of interdependence of critical resources - Bojanić, Dragan J.; Bojanić, Marina M.; Platiša, Jasmina G.; Ristić, Vladimir V.; Mihajlović, Dejan D. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Destabilization of critical resources (CRs) or critical infrastructure (CI) important for the stability of the state can be dangerous for society, economy, and especially national security. Disruption of one CI object or one of its parts often affects and causes disruption of other dependent CI, because the modern society has become a "networked society". The paper proposes a model for quantifying and defining the interdependence between different CIs and their priorities, based on statements of experts. Methods: The proposed methods that combine the Laboratory for Testing and Evaluation of Decision Making (DEMATEL) and the Analytical Network Process (ANP) have been successfully modified by fuzzy logic theory in this work. Results: Integrating multiple methods into a unique input data analysis model significantly affects the change in ranking. Conclusion: The work contributes to military science in making strategic decisions related to national security management through increasing the resilience of CRs and the societies that rely on them.
Keywords: fuzzy logic; DEMATEL; ANP; MCDM; resources; national security